Konsep Ilmu Menurut Fakhr al-Din al-Razi - Tistigar Sansayto; Alinda Zakiyatul Fakhiroh (Universitas Darussalam Gontor, 2018)
The concept of science is related to epistemology, because epistemology is the theory of science. The problem in this modern century, discussion on epistemology suggests a dividing line between science and religion. All science must be empirical in nature, in which brings human understanding into nihilism, relativism and materialism, which is a milestone in the emergence of seculerism and other issues. Then, what is science according to Islam? What are the basic and primacy of it? How does Islam look at sources of right science? How the way of reaching it? Is there any classification of science in Islam? This paper will attempt to answer and discuss these questions clearly and pithily in Fakhr al-Din al-Razi’s perspective. In this regard, al-Razi sees that science is an understanding which delivered on the wisdom of anything, no doubt that science on ru>h, further delivering on perfect happinest. In addition, in his book al-Tafsīr al-Kabīr, Fakhr al-Din al-Razi explains that science has a semblance of meaning with 30 other terms i.e. al-Idrāk, al-Syu'ūr, al-Tasawwur, al-Hifz, al-Tadzakkur, al-Dzikr, al-Ma'rifah, al-Fahm, al-Fiqh, al-'Aql, al-Dirāyah, al-Hikmah, 'ain al-Yaqīn, al-Dzihn, al-Fikr, al-Hadi>ts, al-Dzakā', al-Fata>nah, al-Khātir, al-Zan, al-Tanbīh, al-Khayāl, al-Badīhah, al-Auliyyāt, al-Ruwayyah, al-Kiyāsah, al-Khibrah, al-Ra'yu, al-Firāsah, and al-Bayyinah. From this brief exposure, in tries to discuss the uniqueness of Fakhr al-Din al-Razi thought about science concept using two approaches, philosophy and tafsir, to make it more interesting topic.